Sex work politics : from protest to service provision - Majic, Samantha (American governance., 2014)
Samantha Majic investigates the way two San Francisco-based nonprofit organizations negotiate their governmental obligations while maintaining their commitment to outreach and advocacy for sex workers' rights as well as broader socio-political change.